Assessing Knowledge About Post Discharge Care Among Patients with Myocardial Infarction - Shaheen Sherali; Badil; Hakim Shah; Arsaslan Siddiqui (Journal of the Dow University of Health Sciences, 2007)
Objectives: The aim of this study is to reveal myocardial infarction patient’s responsiveness regarding their post discharge care and to identify need for the betterment in public sector hospital Karachi. Materials & methods: Hospital based cross sectional study was conducted in Karachi Institute of Heart Disease from November 2014 to January 2015. Two hundred patients who had already been admitted with myocardial infarction were approached through purposive sampling method. Data was collected by using pre-tested and self-developed questionnaire. Patients’ knowledge was measured on three areas of main domain like medication, diet, and activity. Data was entered and analyzed in SPSS version 21. Results: 200 patients, 106 (53%) males and 68 (34%) females accounted for insufficient information about their medication clues, doses and then outcome. 12 (06%) males and 06 (03%) females showed better diatery knowledge by giving all accurate answers about the intake of white meat (chicken, and fish), vegetables and salt intake. Only 03 (1.5%) males held ordinary knowledge about physical doings they ought to carry out after they get discharged. Most of the study participants had unsatisfactory knowledge on medications, diet, and activity which they were supposed to do after discharge at home in order to maintain their health. Current study findings designated that quality progress strategies are direly needed to be performed as per discharge education to the patients. Conclusion: Myocardial infarction is fatal or (life threatening), however condition can be averted by utilizing secondary prevention strategies.